E-romance - Praprotnik, Tadej (Monitor ISH, 2005)
E-Romances. The article deals with the issue of establishing and maintaining on-line relationships, especially in chat-rooms, discussion forums or by electronic mail. The topic is illustrated with a number of examples. Due to the (at least partly) different communication context (anonymity, the absence of some elements of normal, face-to-face conversation), such relationships tend to develop in a slightly different way than the classic face-to-face love-affairs or friendships. The author suggests that on-line partners may experience a process of "passivisation", since conflicts can be ascribed simply to the "limiting" medium (i.e. computer-mediated communication).
Keywords: internet; communication; komuniciranje; klepetalnice; e-forumi; elektronska pošta; sociologija komunikacij